KAJIAN PENINGKATAN PENDAPATAN PENGRAJIN GULA KELAPA DI DESA PURBOSARI KECAMATAN SELUMA BARAT KABUPATEN SELUMA - Sriyoto, Sriyoto; Sumantri, Bambang (Jurnal AGRISEP, 2016)
Coconut sugar is one commodity that has potential importance in the composition of the food in the community. Viewed in terms of quality, the quality of the products are still not equal among the producers. This causes the bargaining position of producers becomes weak and coconut sugar prices tend to be low. Seluma Regency especially Western Seluma District has fertile lowland areas and is one of the main producers of coconut sugar precisely in Purbosari village. This study aimed to determine the income level and income-raising efforts of coconut sugar producers in the Purbosari village, Western Seluma District, Seluma Regency. Location of the study was set intentionally (purposive). Data taken in this study were derived from the primary data (interviews) and secondary data (through literature). This study used survey method and the method of selecting the sample in this study was calculated using census. The data analysis used in this study were a quantitative and qualitative analysis. Quantitative analysis was used to calculate the income of coconut sugar producers and qualitative analysis conducted through a descriptive approach. Based on the research discovered that the average income of coconut sugar producers was Rp715.569,60 per week / 40 trees. Common difficulties faced by coconut sugar producers were capital, production engineering, business management and marketing network. Seluma local governments can play a role in efforts to increase the income of coconut sugar producers by providing them with capital, appropriate technology, improved knowledge of entrepreneurship and innovation, as well as business management assistance.